Ambiente laboral y el compromiso organizacional en el Colegio Nacional de Iquitos 2022 - Sajamí Vargas, César Augusto (2023)
The general objective of the research was to determine the relationship between the work environment and the Organizational commitment in the National College of Iquitos, 2022, where an applied type study was chosen, with a correlational level and a non-experimental design, made up of a population of 31 administrators from institution. For data collection, the survey technique has been used, using a questionnaire of questions. The work concluded that the work environment is qualified by 26%, because sometimes the environments of the institution maintain an ideal temperature, and encourage respect for the organizational hierarchy, but the institution almost never issues information necessary to the efficient development of work. However, the organizational commitment is qualified as regular by 29%, since they rarely feel proud of working in said institution and undecided with job stability, and remain loyal to the institution. Likewise, it was determined that the work environment is related to the organizational commitment with a coefficient of 0.791 Rho Spearman, as it was also established that the affective dimension contrasts a correlation coefficient of 0.598; for the continuity dimension a correlation coefficient of 0.635, and normative dimension a correlation coefficient of 0.565, both are significantly related to the work environment.